Geographies of Dirty Water: Landscape-Scale Inequities in Coastal Access in Rhode Island - Twichell, Julia H.; Mulvaney, Kate K.; Merrill, Nathaniel H.; Bousquin, Justin J. (Frontiers in Marine Science, 2022)
Across the United States, development, gentrification, and water quality degradation have altered our access to the coasts, redistributing the benefits from those spaces. Building on prior coastal and green space access research, we examined different populations’ relative travel distances to all public coastal access and to public marine swimming beaches across the state of Rhode Island, by race, ethnicity, and socioeconomics. Next, we assessed relative travel distances to high quality public coastal amenities, i.e., sites with no history of water quality impairment. We used three state-level policy attributes to identify sites with the best water quality: Clean Water Act Section 303(d) impaired waters, shellfishing restrictions, and bacterial beach closure histories. Our analysis revealed statewide disparities in access to Rhode Island’s public coastal amenities. With robust socioeconomic and geographic controls, race and ethnicity remained strongly correlated to travel distance. Higher proportions of Black and Latinx populations in census block groups were associated with longer travel distances to public access, in particular to public coastal sites with better water quality and to public swimming beaches. This translates to added costs on each trip for areas with higher Black and Latinx populations.